Neurological and Olfactory Disturbances After General Anesthesia - Antonino Maniaci; Mario Lentini; Rosario Trombadore; Loris Gruppuso; Santo Milardi; Rosario Scrofani; Giuseppe Cuttone; Massimiliano Sorbello; Rodolfo Modica; Jerome R. Lechien; Paolo Boscolo-Rizzo; Daniele Salvatore Paternò; et al. (Life)
Neurological and olfactory disturbances are increasingly recognized as potential complications of general anesthesia, particularly in vulnerable populations, such as the elderly, children, and individuals with comorbidities. Recent studies have highlighted the need for tailored anesthetic approaches in these high-risk groups to mitigate potential long-term effects. These disturbances, including postoperative cognitive dysfunction, delirium, and olfactory deficits, often arise from shared pathophysiological mechanisms, such as neuroinflammation, oxidative stress, and disruptions in cerebral perfusion. The olfactory system is particularly susceptible to anesthesia-induced neurotoxicity given its proximity to central nervous system structures and its role in sensory and cognitive processing. Furthermore, the unique regenerative capacity of olfactory neurons may be compromised by prolonged or repeated exposure to anesthetic agents, potentially leading to long-term olfactory dysfunction. Risk factors, such as advanced age, neurodegenerative diseases, diabetes, cardiovascular conditions, genetic predispositions, and the type and duration of anesthesia exposure, further exacerbate these complications. Preventive strategies, including comprehensive preoperative risk assessment, personalized anesthetic protocols based on genetic and physiological profiles, and proactive postoperative care with early intervention programs, are critical for reducing impairments and improving long-term patient outcomes. Emerging evidence highlights the potential role of neuroprotective agents, such as antioxidants and anti-inflammatory therapies, in mitigating the effects of anesthesia-induced neurotoxicity. Longitudinal studies are needed to evaluate the long-term effects of anesthesia on cognitive and sensory health, particularly in high-risk populations. These studies should incorporate advanced neuroimaging techniques and biomarker analysis to elucidate the underlying mechanisms of anesthesia-induced neurological and olfactory disturbances. This narrative review provides a comprehensive overview of the mechanisms, risk factors, and preventive strategies for neurological and olfactory disturbances after general anesthesia and highlights future directions for research to improve patient outcomes. We conducted a comprehensive literature search using databases, such as PubMed and Scopus, to identify relevant studies.